2013
DOI: 10.1159/000346564
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Heart Disease: Severity, Associated Anomalies and Parental Decision

Abstract: Objective: This study describes the association between the complexity of congenital cardiac and extracardiac malformations, and the parental decision of pregnancy continuation or termination. Methods: Congenital heart defects (CHD) was diagnosed by ultrasound in 251 fetuses before the 24th week (23 + 6 weeks) of gestation during the four year period from 2007 to 2010. All fetuses from the Utrecht region were referred to our center due to a strict referral pattern. The complexity and severity of the cardiac an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
(32 reference statements)
6
16
0
Order By: Relevance
“…We also showed that these associations were independent of the severity of the CHD, represented by defects unsuitable for biventricular repair. Our results were consistent with those of previous studies [15,17,19,20]. Russo et al showed that termination of pregnancy was [19].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also showed that these associations were independent of the severity of the CHD, represented by defects unsuitable for biventricular repair. Our results were consistent with those of previous studies [15,17,19,20]. Russo et al showed that termination of pregnancy was [19].…”
Section: Discussionsupporting
confidence: 94%
“…Our results were consistent with those of previous studies [15,17,19,20]. Russo et al showed that termination of pregnancy was [19]. In our study, we decided to combine the cases of TOP and CC in the analysis, to assess the direct effect of cytogenetic anomalies and ECMs on parental choice to offer active treatment to their child, and on survival after active treatment.…”
Section: Discussionsupporting
confidence: 91%
“…If true, it be might be expected that this effect would be observed among only or more strongly for infants with critical CHDs, which were more likely to be detected prenatally. 36 Yet, the survival benefit in our study was present nearly equally among infants with critical and noncritical CHDs.…”
Section: Discussionmentioning
confidence: 47%
“…(d) Factors that affect parental decision on TOP : The prenatal diagnosis of major structural abnormalities is one of the main reasons for termination of pregnancy (TOP) worldwide. The decision to continue or terminate the pregnancy has been associated primarily with the severity of the malformation (Asplin et al 2013 ;Nell et al 2013 ) but also with other factors like gestational age at diagnosis (Tararbit et al 2013 ), cultural issues, and the local legal status of TOP. Based on the EUROCAT registry, which provides useful data on overall impact of prenatal screening and testing, Garne et al ( 2005 ) reported on prenatal diagnosis of severe structural congenital malformations in Europe.…”
Section: Diagnosis and Management Of Fetal Structural Abnormalitiesmentioning
confidence: 99%